Análise dos desafios da transformação digital nos pequenos negócios durante a Pandemia COVID-19 no Município de Boa Vista-RR - Trajano, Aline Daíse Louvera (2022)
As with the speed at which information is disseminated through the digital world, digital transformation is necessary in business to keep up with customer expectations and competitiveness in the market. In line with this process, the COVID-19 pandemic, which began in 2020, brought economic and behavioral impacts that required organizations to quickly adapt to the new scenario. This research is characterized as exploratory and descriptive, with a qualitative and quantitative approach, which analyzed and mapped the main challenges for implementing the digital transformation during the COVID-19 pandemic through the application of questionnaires in a sample of 244 small businesses in Boa Vista – RR. Our results showed a 41% increase in adherence to on-line sales of products during the pandemic, as well as it was observed that 50% of entrepreneurs already use digital tools to manage their business. However, a total of 66% of the micro and small companies consulted did not receive technical assistance and/or specialized consultancy during this period. In this sense, this study demonstrates the need to stimulate the dissemination of technical knowledge about digital transformation aiming those small businesses can strategically plan the digitization of their processes. Finally, the results collected and analyzed in this work served as a basis for the development of a detailed manual of digital transformation for micro and small companies, which should contribute to the local and national business community, presenting technological solutions and tools that can meet the needs cited in this research.